Literary-Aesthetic Views of Nazar Eshonqul - Burkhanova Feruza Abdurazzokovna; Saidakhmedova Madinabonu Saidazimovna (Genius Publishing Group, 2023)
In this article, the ideological-artistic features of the novel “Taqiq Mevasi” by the talented novelist Nazar Eshanqul, the symbolism, syncretism, metaphorical, spiral expression characteristic of the writer's style, and the reference to mythological motives are analyzed. In the novel, the creation of man, his actions, the merciless struggle between the merciful and the devil, and the greatness of divine love are written. In the novel, the writer tried to describe the religious and theological content of today's time, closely related to the faith and fate of mankind, in parallel lines. It is explained by scientific theoretical analysis that it aims to warn that the fate of mankind is condemned to eternal and eternal prohibition and sin
Keywords: Literature; detail